Growth, flowering, corm yield and corm-rot incidence as affected by level and frequency of potassium application in gladiolus (Gladiolus grandiflorus) - SINGH, K P; RAMACHANDRAN, N; UMA, S (The Indian Journal of Agricultural Sciences, 2013)
Significantly higher corm weight and less incidence of corm rot were noticed when potassium was applied @ 100 kg/ha to ’Pink Friendship’ gladiolus (Gladiolus grandiflorus L.). But significantly higher number and weight of cormels/ plant were obtained when K was applied @ 200 kg/ha. Other parameters like vegetative growth and floral characters were not significantly influenced by graded levels and their methods of potassium application. The interactions between graded levels and methods of potassium. application were non-signicicant for all the parameters studied.